2012
DOI: 10.1038/nature11697
|View full text |Cite
|
Sign up to set email alerts
|

Bright radio emission from an ultraluminous stellar-mass microquasar in M 31

Abstract: A subset of ultraluminous X-ray sources (those with luminosities of less than 10(40) erg s(-1); ref. 1) are thought to be powered by the accretion of gas onto black holes with masses of ∼5-20M cicled dot, probably by means of an accretion disk. The X-ray and radio emission are coupled in such Galactic sources; the radio emission originates in a relativistic jet thought to be launched from the innermost regions near the black hole, with the most powerful emission occurring when the rate of infalling matter appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 37 publications
(14 reference statements)
2
125
0
Order By: Relevance
“…This is further confirmed by the detection of a classic sub-Eddington thermal dominant (high/soft) state when the X-ray luminosity drops below ∼10 39 erg s −1 . Then, using the constraints on the Eddington luminosity, Middleton et al (2013) estimate a black hole mass of ∼10 M . Also, Liu et al (2013) confirm a probable Wolf-Rayet companion star to a supersoft ULX in M101.…”
Section: Introductionmentioning
confidence: 99%
“…This is further confirmed by the detection of a classic sub-Eddington thermal dominant (high/soft) state when the X-ray luminosity drops below ∼10 39 erg s −1 . Then, using the constraints on the Eddington luminosity, Middleton et al (2013) estimate a black hole mass of ∼10 M . Also, Liu et al (2013) confirm a probable Wolf-Rayet companion star to a supersoft ULX in M101.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of a long super-Eddington accretion phase in 3XMM J150052.0+015452 was strongly supported by the generally quasi-soft X-ray spectra, whose characteristic temperatures are too high to be explained by the standard thermal thin disk below the Eddington limit, but are consistent with Comptonized emission from a low-temperature optical thick corona. Similar spectra are commonly seen in ultraluminous X-ray sources (ULXs) (Gladstone et al 2009;Lin et al 2013b;Middleton et al 2013), most of which are believed to be super-Eddington accreting stellar-mass BHs, except that 3XMM J150052.0+015452 had orders of magnitude higher luminosities.…”
Section: The Tde Explanationmentioning
confidence: 76%
“…On the other hand, as for the outbursts in the low mass X-ray binary (LMXB) transients, no saturation of the peak luminosity, up to the Eddington luminosity, is seen in the relation between the X-ray outburst peak luminosity and the orbital period in the Galactic transients (Wu et al 2010). These empirical relations suggested that some stellar mass compact objects can turn into ultra-luminous X-ray sources during brighter outbursts of similar duration or shorter outbursts (Yu & Yan 2009), which has been indeed observed (Middleton et al 2013). The correlation between the peak power of episodic jet and the corresponding peak luminosity of the soft state in Galactic sources suggests that the investigation of the relation between the episodic jet power and the peak luminosity of the soft state in transient ULXs would tell us about the nature of the ULXs as compared with the Galactic black hole transients; whether ULXs contains intermediate mass black holes or just extreme versions of the Galactic microquasars.…”
Section: Extension To Ultra-luminous X-ray Sources In Nearby Galaxiesmentioning
confidence: 88%
“…In order to address this question, we have investigated two transient ULXs in which radio emission from episodic jet has been detected during their outbursts. One of the ULXs is XMMU J004243.6+412519, which was first detected by XMM-Newton on 15 January 2012 (Henze et al 2012) as an ultra-luminous stellarmass microquasar (∼ 10 M⊙, see Middleton et al 2013) in M31, at a distance of only 0.78 Mpc away from us. Bright radio emission was observed from this source with similar behaviour to those Galactic black hole binaries (Middleton et al 2013).…”
Section: Extension To Ultra-luminous X-ray Sources In Nearby Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation